The Influence of Promotion and User Experience on Purchasing Decisions Through Purchase Interest on Bukalapak - Nurfadillah, Nurfadillah; Anwar , Anwar; aswar, nurul fadilah; musa, chalid imran; haeruddin, ilham wardhana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to evaluate the influence of promotion and user experience on purchasing decisions, with purchase interest as a mediating variable, on the e-commerce platform Bukalapak. The focus of the research is to identify the key factors influencing purchase interest and the relationships between variables in influencing purchasing decisions. A quantitative approach was used with a survey method, by distributing questionnaires to 114 respondents in Makassar City who are users of Bukalapak. Data analysis was conducted using SmartPLS with the Partial Least Square (PLS) technique. The results of the study show that promotion and user experience significantly influence purchasing decisions. User experience also significantly affects purchase interest, while the effect of promotion on purchase interest is not significant. Purchase interest has been proven to play an important role in driving purchasing decisions. Additionally, user experience influences purchasing decisions through purchase interest, while promotions do not show a significant effect through purchase interest.